1996
DOI: 10.1161/01.res.79.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Glycogenolysis Reduces Glycolytic Catabolite Accumulation During Ischemia in Preconditioned Rat Hearts

Abstract: Prior transient episodes of ischemia ("ischemic preconditioning") reduce lactate accumulation and attenuate acidosis during a subsequent prolonged ischemic insult. The mechanisms responsible for attenuated glycolytic catabolite accumulation have not been established but may include earlier exhaustion of glycogen stores, slowed glycogenolysis before complete glycogen depletion, and/or inhibition of glycolysis. Simultaneous repeated measures of myocardial glycogen and the rates of glycolysis, glycogenolysis, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 49 publications
2
23
1
2
Order By: Relevance
“…Thus, preconditioning, as well as its association with postconditioning prevented the depletion of glycogen storage caused by ischemic process. These results are similar to those of Weiss et al 22 and Pescador et al 23 . The exact molecular mechanism to explain this phenomenon is yet to be understood.…”
Section: Ischemic Pre and Postconditioning In Skeletal Muscle Injury supporting
confidence: 93%
“…Thus, preconditioning, as well as its association with postconditioning prevented the depletion of glycogen storage caused by ischemic process. These results are similar to those of Weiss et al 22 and Pescador et al 23 . The exact molecular mechanism to explain this phenomenon is yet to be understood.…”
Section: Ischemic Pre and Postconditioning In Skeletal Muscle Injury supporting
confidence: 93%
“…The role of myocardial glycogen breakdown in the cardioprotection observed with preconditioning is controversial: one study reported that ischemic preconditioning attenuated glycogenolysis in rat hearts (99), whereas another study showed that 24-h in vivo fasting resulted in increased glycogen content and greater glycogen utilization during ischemia/reperfusion in a Langendorff model (80), attributed to activation of phosphorylase a (94). Interestingly, it was also observed that insulin pretreatment increased glycogen content to a similar extent but suppressed glycogen utilization during ischemia/reperfusion, resulting in increased injury and function (80).…”
Section: Mitochondrial Clearance (Mitophagy) and Mitochondrial Sequesmentioning
confidence: 99%
“…36,37,42,43 Diazoxide is also shown to significantly reduce intracellular acidification during ischemia. Attenuation of the decline in pH i during ischemia has been attributed to (1) inhibition of H ϩ production secondary to a reduction in glycolysis or glycogenolysis 43 or, alternatively, to preischemic glycogen depletion, and (2) increased H ϩ extrusion to the extracellular space, lowering pHo but attenuating the intracellular acidification. However, arguing against the hypothesis that preconditioning enhances H ϩ extrusion, Gabel et al 42 found that preconditioning attenuated the fall in both pHi and pHo.…”
Section: Attenuation Of Ischemic Acidification By Diazoxidementioning
confidence: 99%